Explanations for apparent late onset criminality in a high-risk sample of children followed up in adult life - Pickles, Andrew; Rutter, Michael; Simonoff, Emily (The British journal of criminology, 2000)
We examined the psychiatric and forensic histories of 13 individuals whose first officially recorded criminal conviction took place after their 22nd birthday, and compared the levels of disturbance among that group with those from the same high-risk sample who had (a) no recorded convictions, (b) convictions only up to age 21, and (c) convictions before and after age 22. Among the 13 with recorded convictions only after age 22, there was evidence of at least minor juvenile delinquency in every case but one, and of major adult mental illness whose onset preceded first conviction in four cases. Levels of childhood antisocial behaviours were significantly higher among that group than among those who had never been convicted, and levels of major mental illness were significantly higher than among those who had never been convicted and those with convictions only up to age 21. Apparent late onset criminality in the present sample was therefore associated with known risk factors for adult criminality, in the form of juvenile antisocial behaviour and/or major mental illness